An Analysis of the Role of the Facilitator in the Professional Writing Classroom - Shamsudin, Khatija (Journal of Modern Languages, 2017)
This paper intends to investigate the possible roles for teachers to facilitate the acquisition of written skills by professionals from the business community. Investigation into these roles involves looking at the traditional roles of teachers and outlining some of the commonly practised ones for discussion purposes. The study seeks a profile of learner variables which may affect learning success in which facilitators need to take into consideration when designing a course and conducting classes. It also evaluates critically the traditional roles of teachers in terms or their strengths and weaknesses and discusses the implications for facilitators of professionals writing courses.